Impact of blackboard learning system on cognitive-communication and culture in Saudi Arabia - Hakem Almijlad, Aliyah Kayyad; Muhamad, Mohd Mokhtar; Md Khambari, Mas Nida (Society of Cultural Studies and Social Sciences, 2023)
This study aimed to explore the potential of the blackboard learning system in enhancing cognitive communication between male lecturers and female students. The study used a triangulation method to justify the credibility of the research through the researcher as a primary instrument and interviews. Major findings indicated that there was a lack of training on the use of blackboarding from the student's and lecturers' perspectives. The study has notably contributed to the educational technology field by exploring the blackboard learning system with cognitive communication in a culture-dependent community. There were suggestions from respondents on enhancing the roles of cognitive communication such as creating awareness, developing problem-solving skills, attentiveness, and encouraging executive functions while learning with the blackboard system. The findings enhanced the concept that learning platforms should contain gadgets and programs to become independent with the ability to enhance cognitive communication. The study concluded that enabling effective use of the blackboard learning system influenced effective communication between male lecturers and female students. It was concluded that applying learning platforms such as organizing training, conducting student-teacher meetings, and seminars, and including the positive roles of blackboarding promotes cognitive communication and bridges culture gaps among lecturers and students. It is recommended for future studies conduct similar studies with other types of learning platforms which will subsequently provide additional insights into the phenomenon of cognitive communication in the field of educational technology.